Fertility preservation methods in the context of breast cancer treatment: real-life experience and prospects - A. A. Zagidullina; L. A. Dzhambulatova; M. A. Shatueva; T. B. Dongak; Y. S. Laubakh; D. S. Shakirova; A. S. Golantsev; Kh. R. Payzulaeva; D. P. Yastrebova; A. M. Aksenov; E. S. Goncharova; M. A. Ozhereleva; et al. (Акушерство, гинекология и репродукция)
The article discusses current methods for preserving fertility in women undergoing breast cancer (BC) treatment. It provides a detailed overview of contemporary breast cancer treatments and their impact on fertility. To prevent fertility loss, there are described key strategies such as oocyte, embryo, and ovarian tissue cryopreservation, as well as temporary suppression of ovarian function using gonadotropin-releasing hormone agonists. In addition, it analyzes factors such as lack of information, limited medical resources, and the need for immediate anticancer therapy initiation that hinder access to such methods. The importance of comprehensive patient support systems involving coordination among oncologists, reproductive specialists, and psychologists is emphasized. Special attention is paid to further development and improvement of existing methods aimed at reducing gonadotoxicity, as well as ongoing research to identify new safe and effective strategies. It is specifically stressed about importance of long-term monitoring of children born from preserved gametes and tissues to assess the safety and efficacy of such approaches. Integrating fertility preservation into the overall BC treatment strategy can markedly improve women's quality of life by increasing their chances of regaining reproductive function after completing primary treatment.